2021
DOI: 10.1149/2162-8777/ac39a8
|View full text |Cite
|
Sign up to set email alerts
|

Al Composition Dependence of Band Offsets for SiO2 on α-(AlxGa1−x)2O3

Abstract: Valence band offsets for SiO2 deposited by Atomic Layer Deposition on α-(AlxGa1-x)2O3 alloys with x = 0.26–0.74 were measured by X-ray Photoelectron Spectroscopy. The samples were grown with a continuous composition spread to enable investigations of the band alignment as a function of the alloy composition. From measurement of the core levels in the alloys, the bandgaps were determined to range from 5.8 eV (x = 0.26) to 7 eV (x = 0.74). These are consistent with previous measurements by transmission spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We have recently found that SiO 2 deposited on the α-(Al x Ga 1-x ) 2 O 3 alloys shows band alignments that are staggered type II for x < 0.5 and straddling type I for x > 0.5, with conduction band offsets >1.3 eV across the composition range examined. 72 Even this large gap dielectric will only provide adequate valence band offsets over a limited range of compositions. 72 Note also that we find the bandgap of the ALD Al 2 O 3 is slightly smaller than the α(Al 0.74 Ga 0.26 ) 2 O 3 , which is a common feature when comparing amorphous thin films to polycrystalline films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently found that SiO 2 deposited on the α-(Al x Ga 1-x ) 2 O 3 alloys shows band alignments that are staggered type II for x < 0.5 and straddling type I for x > 0.5, with conduction band offsets >1.3 eV across the composition range examined. 72 Even this large gap dielectric will only provide adequate valence band offsets over a limited range of compositions. 72 Note also that we find the bandgap of the ALD Al 2 O 3 is slightly smaller than the α(Al 0.74 Ga 0.26 ) 2 O 3 , which is a common feature when comparing amorphous thin films to polycrystalline films.…”
Section: Resultsmentioning
confidence: 99%
“…72 Even this large gap dielectric will only provide adequate valence band offsets over a limited range of compositions. 72 Note also that we find the bandgap of the ALD Al 2 O 3 is slightly smaller than the α(Al 0.74 Ga 0.26 ) 2 O 3 , which is a common feature when comparing amorphous thin films to polycrystalline films. [22][23][24][25][26] The optical bandgap of a-Al 2 O 3 single crystal is 8.7-8.8 eV.…”
Section: Resultsmentioning
confidence: 99%
“…46,47) So far, some investigations of the optical properties of α-(Al x Ga 1−x ) 2 O 3 have been made by Ito et al 48) and Jinno et al 38) employing optical transmission measurements. Dang et al 35) analyzed a Tauc plot and Uchida et al 49) Chen et al 36) and Xia et al 50) utilized X-ray photoelectron spectroscopy (XPS) to determine bandgap values and/or bowing parameters. But since the corundum crystal structure is anisotropic, a polarization dependent investigation of the material properties is crucial.…”
Section: Introductionmentioning
confidence: 99%